A spatial homojunction of titanium vacancies decorated with oxygen vacancies in TiO2 and its directed charge transfer. Issue 36 (7th September 2022) - Wu, Si-Ming; Wang, Yi-Tian; Xiao, Shi-Tian; Wang, Li-Ying; Tian, Ge; Chen, Jiang-Bo; Liu, Jia-Wen; Shalom, Menny; Yang, Xiao-Yu
Abstract : The spatial n–p homojunction design in TiO2 greatly enhances its photocatalytic H2 production performance owing to the directed charge transfer. Abstract : The n–p homojunction design in semiconductors could enable directed charge transfer, which is promising but rarely reported. Herein, TiO2 with a spatial n–p homojunction has been designed by decorating TiO2 nanosheets with Ti vacancies around nanostructured TiO2 with O vacancies. 2D 1 H TQ-SQ MAS NMR, EPR and XPS show the junction of titanium vacancies and oxygen vacancies at the interface. This spatial homojunction contributes to a significant enhancement in photoelectrochemical and photocatalytic performance, especially photocatalytic seawater splitting. Density functional theory calculations of the charge density reveal the directional n–p charge transfer path at the interface, which is proposed at the atomic-/nanoscale to clarify the generation of rational junctions. The spatial n–p homojunction provides a facile strategy for the design of high-performance semiconductors.